2020
DOI: 10.1101/2020.01.24.918904
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Local stabilization of subunit-subunit contacts causes global destabilization of Hepatitis B virus capsids

Abstract: AbstractDevelopment of antiviral molecules that bind virion is a strategy that remains in its infancy and the details of their mechanisms are poorly understood. Here we investigate the behavior of DBT1, a dibenzothiazapine, which specifically interacts with the capsid protein of Hepatitis B Virus (HBV). We found that DBT1 stabilizes protein-protein interaction, accelerates capsid assembly, and can induce formation of aberrant particles. Paradoxically, DBT1 can cause pre-formed … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 73 publications
1
7
0
Order By: Relevance
“…In sub-saturating conditions, when HAP fills B and C sites, capsids are stabilized (13). We observe that when there is enough HAP to fill all four classes of site, capsids are destabilized because HAPs disrupt icosahedral geometry (14, 40). We showed that untreated or sub-saturating HAP12 conditions did not increase CTD sensitivity to protease activity in empty capsids.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…In sub-saturating conditions, when HAP fills B and C sites, capsids are stabilized (13). We observe that when there is enough HAP to fill all four classes of site, capsids are destabilized because HAPs disrupt icosahedral geometry (14, 40). We showed that untreated or sub-saturating HAP12 conditions did not increase CTD sensitivity to protease activity in empty capsids.…”
Section: Discussionmentioning
confidence: 91%
“…These small molecules increase the association energy of interdimer contacts (13, 15). However, by locally distorting the interdimer interface, HAPs can disturb global icosahedral geometry (1517, 40, 45, 46). As more HAPs bind, a global cascading effect on capsid structure leads to deformation and eventually disruption (1417, 40).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These variations result from asymmetric capsid motions and distortions due to stochastic thermal fluctuations, which are also reported in previous studies of viral capsids and speculated to be of biological importance for disassembly. 22,30,31 The variability in the average root mean square deviations (RMSDs) of the proteins within the capsid also points to their inherent structural heterogeneity due to thermal fluctuations ( Fig. S3).…”
Section: Resultsmentioning
confidence: 99%